The development and psychometric properties testing of intolerance of uncertainty scale for Indonesian adults - Lovian, Divani Aery; Maulina, Dewi; Ramadina, Hilma; Kusuma, Nathania (Psychological Research on Urban Society, 2023)
Uncertain situations have further exacerbated great vulnerability to stressors and a high risk of mental health problems in urban populations. The adverse effects of uncertainty on well-being have been increasingly concerning and heightened the need to understand intolerance of uncertainty (IU) as a factor that influences responses to uncertainty. However, few scales have been developed to measure IU, especially in Indonesia. To address this concern, the current study aimed to develop a reliable and valid Intolerance of Uncertainty Scale for Indonesian Adults (IUS-A). The scale was developed and validated using data from 588 participants aged 20–65 years (M = 32, SD = 11.04) from various provinces in Indonesia. Confirmatory factor analysis confirmed that the unidimensional IUS-A fit the theoretical model. The final version of the IUS-A consists of 18 items with good internal consistency and a valid measurement of IU. Furthermore, the items exhibited good discriminatory power to differentiate individuals with high and low levels of IU. Based on these results, IUS-A is a reliable and valid instrument for measuring IU in the adult population in Indonesia.